Validation of the Maternal Resilience Scale (ERESMA) in Mothers of Children with Disabilities - Cahuana-Cuentas, Milagros (2025)
Introduction: Maternal resilience is a crucial variable for mothers of children with disabilities; therefore, having instruments grounded in theoretical models that reflect the unique characteristics of this condition is highly relevant. Objective: To analyze the validity and reliability of the Maternal Resilience Scale (ERESMA) in Peruvian mothers of children with disabilities. Method: The study followed an instrumental design, evaluating a sample of 243 mothers of children with disabilities, aged between 23 and 76 (M = 43.16) and living in the provinces of Arequipa and Puno. The diagnoses of their children were mainly intellectual disability (42.7%), autism spectrum disorder (15.3%), and multiple disabilities (15.3%). Results: It was confirmed that the original six-factor structure has adequate goodness-of-fit indices: ꭓ2(804) = 916.222, p = .004, CFI = .985, TLI = .984, RMSEA = .024, and SRMR = .072. Likewise, the internal consistency results using the omega coefficient are adequate for self-determination (ω = .727), hopelessness (ω = .826), spiritual faith (ω = .763), lack of partner support (ω = .836), and limited resources to meet needs (ω = .785); while borderline values were obtained for the factor of rejection personal responsibility (ω = .651). Conclusion: The ERESMA Scale, when applied to mothers of children with disabilities in Peru, demonstrates sufficient evidence of validity and reliability to support its appropriate use.